Method for preparing high-strength high-toughness wear-resistant PcBN cutter from B4C reinforced TiNbZrTa

By using B4C enhanced TiNbZrTa binding agent in PcBN tools and adopting high-temperature and high-pressure sintering process, the problem of degradation in traditional PcBN tools in high temperature and high wear environments is solved, and the strength, toughness and wear resistance of the tool are significantly improved, meeting the demand of modern manufacturing for high-performance tools.

CN119703062AActive Publication Date: 2025-03-28ZYNP GRP DING RUI TECH CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411921718.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The performance of traditional PcBN tools in high temperature and high wear environments is mainly due to the weak binding strength between the binding agent and cBN, and the insufficient strength, toughness and wear resistance of the binding agent at high temperature.

Method used

B4C is used as a reinforcing material and added to PcBN with TiNbZrTa as the binding agent, which significantly improves the overall performance of PcBN through high-temperature and high-pressure sintering process.

Benefits of technology

It significantly improves the strength, toughness and wear resistance of PcBN tools, allowing them to adapt to more demanding processing conditions, extend tool life, and meet the needs of modern manufacturing for high-performance tools.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of manufacturing of superhard materials, and particularly relates to a method for preparing a high-strength, high-toughness and wear-resistant PcBN cutter from B4C reinforced TiNbZrTa. The method comprises the steps that cBN powder of 4-6 microns is subjected to acid-base pretreatment and then evenly mixed with TiNbZrTa powder of 10 microns and B4C powder of 2-4 microns according to a proper proportion, then vacuum drying is conducted, a synthetic mold is filled with the mixture to be assembled into a synthetic block, then the synthetic block is put into a cubic press to prepare a PcBN cutter blank at high temperature and high pressure, and the PcBN cutter is prepared through brazing of the PcBN cutter blank and WC alloy. The process is simple and controllable, operation is easy, efficiency is high, cost is low, large-scale industrial production can be met, the service life of the PcBN cutter can be remarkably prolonged, and the PcBN cutter has excellent performance especially when high-temperature alloy, hard alloy and other difficult-to-machine materials are machined.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of superhard material manufacturing, and in particular relates to a method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool by using B4C-reinforced TiNbZrTa. Background Art

[0002] In the current manufacturing industry, higher and higher requirements are placed on the performance of tool materials, especially in the field of high-speed and high-precision machining. Polycrystalline cubic boron nitride (PcBN) not only has high hardness, but also has good thermal and chemical stability, and does not react with iron-containing materials at high temperatures, making it an ideal choice for processing iron cluster materials. However, in the face of high temperature and high wear environments, there is still a problem of performance degradation, mainly because the bonding strength between the binder and cubic boron nitride (cBN) in traditional PcBN tools is weak, and the strength, toughness and wear resistance of the binder itself at high temperatures cannot meet the requirements, limiting its application range and efficiency. In order to solve this problem, people have been seeking various methods to improve the performance of the binder itself and the bonding performance between the binder and cBN, so as to improve the overall performance of PcBN tools and broaden their application areas.

[0003] Since the surface of cBN particles is smooth and the surface energy is high, the wettability with metal is poor, resulting in only a weak physical bond between cBN particles and metal binder, making the holding force between metal binder and cBN particles weak, and the strength and hardness of metal binder at high temperature will decrease, resulting in reduced performance of PcBN tools at high temperature.

[0004] High Entropy Alloys (HEAs), also known as multi-component alloys, baseless alloys, concentrated solid solution alloys and alloys with complex composition, and the atomic content of each element is between 5% and 35%, breaking the design concept of traditional alloys based on one or two metal elements. It has "four major effects", namely, high entropy effect in thermodynamics, lattice distortion effect in structure, hysteresis diffusion effect in dynamics and "cocktail" effect in properties, showing high strength, high hardness, high wear resistance, high fracture toughness, excellent low temperature performance and structural stability, good corrosion resistance and oxidation resistance, and is used in aerospace, automotive industry, electronics industry, nuclear energy and other military applications, medical equipment, energy conversion and storage and other fields. Among the many high entropy alloy systems, TiNbZrTa series high entropy alloys are difficult to dissolve high entropy alloys.

[0005] Boron carbide (B4C), also known as black diamond, is an inorganic substance with the chemical formula B4C. It is usually a gray-black powder and is one of the three hardest materials known (after diamond and cubic boron nitride). It is used in tank armor, bulletproof vests and many industrial applications. B4C has the following specific performance characteristics: (1) High hardness: Its Mohs hardness is about 9.5, second only to diamond, and is suitable for manufacturing wear-resistant materials; (2) High strength: Its compressive strength and flexural strength are very high, suitable for high stress environments; (3) Low density: Compared with other common shielding materials, B4C has a lower density, which is convenient for transportation and installation; (4) Good neutron absorption ability: B4C has a significant shielding effect on fast neutrons and is often used in nuclear reactors and radiation protection; (5) High temperature stability: B4C can still maintain good performance at high temperatures and is suitable for high temperature working environments; (6) Anti-oxidation: B4C has good anti-oxidation properties and can be used in harsh environments; (7) Corrosion resistance: B4C performs well in corrosive media such as acids and alkalis and has good chemical stability. Because boron carbide has the above excellent properties, it is widely used in military industry, nuclear industry, engineering and other fields.

[0006] However, in the prior art, there is no method for preparing high-strength, high-toughness and wear-resistant PcBN cutting tools using ultrafine B4C and TiNbZrTa. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing high-strength, high-toughness and wear-resistant PcBN tools by B4C reinforced TiNbZrTa, by adding B4C as a reinforcing material to PcBN prepared with TiNbZrTa as a binder to significantly improve the overall performance of PcBN, thereby preparing high-strength, high-toughness and wear-resistant PcBN tools, so that the PcBN tools can adapt to more stringent processing conditions and meet the needs of modern manufacturing industry for high-performance tools.

[0008] In order to achieve the above object, the present invention adopts the following technical solutions:

[0009] A method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool by using B4C-reinforced TiNbZrTa, characterized in that it comprises the following steps:

[0010] S1. Select raw materials, which include the following components by mass percentage: 80%-85% main crystal phase, 13%-19.5% binder, and 0.5%-2.0% reinforcing agent; wherein the main crystal phase is cBN powder, the binder is TiNbZrTa powder, and the reinforcing agent is B4C powder;

[0011] S2, mixing, adding the main crystal phase, binder and reinforcing agent into the solvent in proportion and mixing evenly to obtain a mixed slurry, placing the obtained mixed slurry in a vacuum drying oven for drying and high temperature treatment to obtain a mixed powder;

[0012] S3, sintering, filling the mixed powder into a synthesis mold to form a synthesis block, sintering at high temperature and high pressure in a six-sided top press according to the set process parameters, unloading the pressure and cooling to room temperature to obtain a PCBN sample;

[0013] S4. Brazing the PcBN sample sintered at high temperature and high pressure with the WC alloy substrate to obtain a PcBN tool.

[0014] Preferably, the cBN powder has a grain size of 4 μm-6 μm and a purity of 99.9%.

[0015] Preferably, the TiNbZrTa powder has a grain size of 10 μm and a purity of 99.9%.

[0016] Preferably, the B4C powder has a grain size of 2 μm-4 μm and a purity of 99.9%.

[0017] Preferably, in step S1, the cBN powder is first placed in a 10% to 30% dilute hydrochloric acid solution, boiled for 10 min-50 min, and then washed with distilled water, then placed in a 10% to 30% NaOH solution, also boiled for 10 min-50 min, and then washed with distilled water, and then after centrifugation, first washed with distilled water, then washed with anhydrous ethanol, and finally vacuum dried for standby use.

[0018] Preferably, in step S2, a ball mill is used for mixing, and in the ball mill, the weight ratio of the solvent, the raw material, and the grinding balls is 2:1:3, the mixing time is 24h to 30h, and the grinding balls are zirconia balls or cemented carbide balls.

[0019] Preferably, in step S2, the solvent is anhydrous ethanol.

[0020] Preferably, in step S2, the drying is carried out at 3.0×10 -3 The samples were dried under vacuum at 60°C for 24 h.

[0021] Preferably, in step S2, the high temperature treatment is performed at 3.0×10 -3 Pa in a vacuum environment and treated at a temperature of 500°C-600°C for 1h-3h.

[0022] Preferably, the process parameters of the high temperature and high pressure sintering in step S3 are: sintering pressure of 5-6 GPa, sintering temperature of 1450° C.-1550° C., and holding time of 5 min-10 min.

[0023] The present invention also includes other steps that enable it to be used normally, which are all conventional technical means in the field; in addition, the steps not limited in the present invention all adopt conventional means in the field and will not be described in detail here.

[0024] The working principle of the present invention is:

[0025] The present invention uses high entropy alloy TiNbZrTa powder to replace general metal binders. In the process of preparing PcBN tools at high temperature and high pressure, components in TiNbZrTa react with B and N atoms in cBN to generate TiB2, ZrN, TiN, TaN, and Nb2B3, respectively. These reaction products have high hardness, strength, oxidation resistance, wear resistance, and corrosion resistance. Moreover, since these elements react chemically with B and N atoms in cBN during the preparation process, the bond between cBN and the binder is a chemical bond, and the chemical bond energy is relatively high, so that the bonding force between cBN and the binder is relatively high, and the overall performance of the PcBN tool can be improved.

[0026] The present invention uses fine crystals to improve the strength, hardness and toughness of the material. The 10μm TiNbZrTa powder and the 4μm-6μm cBN powder can not only improve the strength of the binder itself and the bonding strength between the binder and cBN, but also improve the toughness of the PcBN tool, thereby enhancing the overall performance of the PcBN tool.

[0027] The B4C powder used in the present invention has excellent wear resistance and corrosion resistance. It is added as a reinforcing material to PcBN prepared with TiNbZrTa powder as a binder, which can significantly improve the overall performance of PcBN, thereby preparing high-strength, high-toughness, ultra-hard and wear-resistant PcBN tools, so that the PcBN tools can adapt to more stringent processing conditions and meet the needs of modern manufacturing industry for high-performance tools.

[0028] When the above materials are sintered in appropriate proportions and with suitable high temperature and high pressure processes, high strength, high toughness and wear resistance of cBN itself, high strength, high toughness, wear resistance and corrosion resistance of TiNbZrTa, and high temperature and high pressure processes can be used to obtain high-strength, high-toughness and wear-resistant PcBN tools.

[0029] The beneficial effects of the present invention are:

[0030] The process of the present invention is simple, controllable, easy to operate, highly efficient, and low in cost, and can meet the requirements of large-scale industrial production. It utilizes the high hardness of cBN itself, the high strength, high hardness, and high fracture toughness of TiNbZrTa, and the high hardness, high strength, low density, high temperature stability, and good anti-oxidation characteristics of B4C. Moreover, the elements in TiNbZrTa can react with B and N atoms in cBN to generate TiB2, ZrN, TiN, TaN, and Nb2B3, respectively. These nitrides and borides have high hardness, strength, and wear resistance. In addition, due to the chemical reaction that occurs under high temperature and high pressure, the combination between cBN and TiNbZrTa is transformed into a chemical bond combination, so that the bonding force between cBN and the binder is relatively high, which can improve the overall performance of the PcBN tool, thereby significantly improving the life of the PcBN tool, especially when processing difficult-to-process materials such as high-temperature alloys and cemented carbides, showing excellent performance. DETAILED DESCRIPTION

[0031] The present invention is further described below with specific examples. The illustrative embodiments and descriptions of the present invention are used to explain the present invention, but are not intended to limit the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work, any modifications, equivalent substitutions, improvements, etc., should be included in the protection scope of the present invention.

[0032] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0033] The devices used in the present invention are not particularly limited and can be any of the commonly used devices in the art.

[0034] Example 1

[0035] A method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool by using B4C-reinforced TiNbZrTa, comprising the following steps:

[0036] S1. Select raw materials, which include the following components by mass percentage: 85% main crystal phase, 14% binder, and 1% reinforcing agent; wherein the main crystal phase is cBN powder, with a grain size of 4μm-6μm and a purity of 99.9%. The binder is TiNbZrTa powder, with a grain size of 10μm and a purity of 99.9%. The reinforcing agent is B4C powder, with a grain size of 2μm-4μm and a purity of 99.9%.

[0037] In this embodiment, cBN powder was purchased from Zhengzhou Zhongnan Jet Superhard Materials Co., Ltd., model CBNM-W, TiNbZrTa powder was purchased from Beijing New Materials Research Institute, and B4C powder was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0038] S2, mixing, adding the main crystal phase, binder and reinforcing agent into the solvent in proportion and mixing evenly to obtain a mixed slurry, placing the obtained mixed slurry in a vacuum drying oven for drying and high temperature treatment to obtain a mixed powder;

[0039] S3, sintering, filling the mixed powder into a synthesis mold to form a synthesis block, sintering at high temperature and high pressure in a six-sided top press according to the set process parameters, unloading the pressure and cooling to room temperature to obtain a PCBN sample;

[0040] S4. Brazing the PcBN sample sintered at high temperature and high pressure with the WC alloy substrate to obtain a PcBN tool.

[0041] In step S1, the cBN powder is first placed in a 30% dilute hydrochloric acid solution, boiled for 30 minutes, and then washed with distilled water. It is then placed in a 30% NaOH solution, boiled for 30 minutes and washed with distilled water. After centrifugation, it is first washed with distilled water, then washed with anhydrous ethanol, and finally vacuum dried for use.

[0042] In step S2, a high-energy ball mill is used for mixing, the speed is 300 r / min, the mixing time is 24 h, and the weight ratio of the solvent, raw material, and grinding ball in the high-energy ball mill is 2:1:3, and the grinding ball is a zirconia ball. The solvent is anhydrous ethanol. The drying is carried out at 3.0×10 -3 Pa vacuum and 60°C vacuum drying for 24 h. -3 Pa in a vacuum environment and treated at 500°C for 3h.

[0043] The process parameters of high temperature and high pressure sintering in step S3 are: sintering pressure is 5.0 GPa, sintering temperature is 1450° C., and holding time is 10 min. After sintering, the sample is taken out by cooling and releasing the pressure, and the surface of the sample is polished and processed.

[0044] The PcBN sample prepared in Example 1 was subjected to performance testing. The test process used the FM-ARS900 semi-automatic microscopic measurement system of Japan's Future-Tech Company. The microhardness of the sample was measured at a pressure of 30N for 15s, and the fracture toughness was calculated based on the crack size. The flexural strength of the sample was measured using a WDW-50 universal electronic material testing machine. The sample wear ratio was measured by grinding a green SiC grinding wheel using a domestic MA6025 universal tool grinder. Specific test results: The flexural strength, microhardness and fracture toughness values ​​of PcBN were 602MPa, 44.88GPa and 6.53MPa·m, respectively. 1 / 2 , wear ratio 7352.

[0045] Example 2

[0046] The difference between this embodiment and embodiment 1 is that in step S1, the raw materials include the following components by mass percentage: 80% main crystal phase, 19.5% binder, and 0.5% reinforcing agent; in step S2, when mixing the materials, the grinding balls are cemented carbide balls. The high temperature treatment is carried out at 3.0×10 -3 Pa in a vacuum environment and at a temperature of 550° C. for 2 hours. The process parameters of the high temperature and high pressure sintering in step S3 are: sintering pressure of 5.5 GPa, sintering temperature of 1500° C., and holding time of 8 minutes.

[0047] The performance test of the PcBN sample prepared in Example 2 was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness of PcBN are 625MPa, 43.71GPa and 6.67MPa·m 1 / 2 , the wear ratio is 7521.

[0048] Example 3

[0049] The difference between this embodiment and embodiment 1 is that in step S1, the raw materials include the following components by mass percentage: 80% main crystal phase, 18% binder, and 2% reinforcing agent; in step S2, when mixing the materials, the grinding balls are cemented carbide balls. The high temperature treatment is carried out at 3.0×10 -3 The sintering process is carried out under a vacuum environment of 5.5 GPa and at a temperature of 600°C for 1 hour. The process parameters of the high temperature and high pressure sintering in step S3 are: sintering pressure of 5.5 GPa, sintering temperature of 1500°C, and holding time of 5 minutes.

[0050] The performance test of the PcBN sample prepared in Example 3 was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness of PcBN are 621 MPa, 42.81 GPa and 7.12 MPa·m 1 / 2, the wear ratio is 7636.

[0051] Example 4

[0052] The difference between this embodiment and embodiment 1 is that in step S1, the raw material includes the following components by mass percentage: 85% main crystal phase, 13% binder, and 2% reinforcing agent. In step S2, the mixing time is 30 hours, and the process parameters of high temperature and high pressure sintering in step S3 are: sintering pressure is 6.0 GPa, sintering temperature is 1480°C, and holding time is 10 minutes.

[0053] The performance test of the PcBN sample prepared in Example 4 was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness of PcBN are 632MPa, 44.28GPa and 6.91MPa·m 1 / 2 , the wear ratio is 7621.

[0054] Example 5

[0055] The difference between this embodiment and embodiment 1 is that in step S1, the raw material includes the following components by mass percentage: 83% main crystal phase, 15% binder, and 2% reinforcing agent. In step S2, the mixing time is 28 hours, and the process parameters of high temperature and high pressure sintering in step S3 are: sintering pressure is 6.0 GPa, sintering temperature is 1550°C, and holding time is 7 minutes.

[0056] The performance test of the PcBN sample prepared in Example 5 was carried out according to the same test method as in Example 1. The specific test results are as follows: the bending strength, microhardness and fracture toughness of PcBN are 653 MPa, 43.86 GPa and 7.25 MPa·m 1 / 2 , the wear ratio is 7687.

[0057] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing high-strength, high-toughness and wear-resistant PcBN cutting tools by B4C-reinforced TiNbZrTa, characterized in that: The following steps are involved: S1. Select raw materials, which include the following components by mass percentage: 80%-85% main crystal phase, 13%-19.5% binder, and 0.5%-2.0% reinforcing agent; wherein the main crystal phase is cBN powder, the binder is TiNbZrTa powder, and the reinforcing agent is B4C powder; S2, mixing, adding the main crystal phase, binder and reinforcing agent into the solvent in proportion and mixing evenly to obtain a mixed slurry, placing the obtained mixed slurry in a vacuum drying oven for drying and high temperature treatment to obtain a mixed powder; S3, sintering, filling the mixed powder into a synthesis mold to form a synthesis block, sintering at high temperature and high pressure in a six-sided top press according to the set process parameters, unloading the pressure and cooling to room temperature to obtain a PCBN sample; S4. Brazing the PcBN sample sintered at high temperature and high pressure with the WC alloy substrate to obtain a PcBN tool.

2. The method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool by using B4C-reinforced TiNbZrTa according to claim 1, characterized in that: The grain size of the cBN powder is 4 μm-6 μm, and the purity is 99.9%.

3. The method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool by using B4C-reinforced TiNbZrTa according to claim 2, characterized in that: The grain size of the TiNbZrTa powder is 10 μm, and the purity is 99.9%.

4. The method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool by using B4C-reinforced TiNbZrTa according to claim 3, characterized in that: The grain size of the B4C powder is 2 μm-4 μm, and the purity is 99.9%.

5. The method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool by using B4C-reinforced TiNbZrTa according to claim 4, characterized in that: In step S1, the cBN powder is first placed in a 10% to 30% dilute hydrochloric acid solution, boiled for 10 min to 50 min, and then washed with distilled water. It is then placed in a 10% to 30% NaOH solution, boiled for 10 min to 50 min, and then washed with distilled water. After centrifugation, it is first washed with distilled water, then washed with anhydrous ethanol, and finally vacuum dried for use.

6. The method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool by using B4C-reinforced TiNbZrTa according to claim 1, characterized in that: In step S2, a ball mill is used for mixing, and the weight ratio of the solvent, the raw material, and the grinding balls in the ball mill is 2:1:3, and the mixing time is 24h to 30h. The grinding balls are zirconia balls or cemented carbide balls.

7. The method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool by using B4C-reinforced TiNbZrTa according to claim 6, characterized in that: In step S2, the solvent is anhydrous ethanol.

8. The method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool by using B4C-reinforced TiNbZrTa according to claim 6, characterized in that: In step S2, the drying is carried out at 3.0×10 -3 The samples were dried under vacuum at 60°C for 24 h.

9. The method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool by using B4C-reinforced TiNbZrTa as claimed in claim 6, characterized in that: In step S2, the high temperature treatment is performed at 3.0×10 -3 Pa in a vacuum environment and treated at a temperature of 500°C-600°C for 1h-3h.

10. A method for preparing a high-strength, high-toughness, and wear-resistant PcBN tool according to any one of claims 1 to 9, characterized in that: In step S3, the process parameters of the high temperature and high pressure sintering are: sintering pressure is 5 GPa-6 GPa, sintering temperature is 1450° C.-1550° C., and holding time is 5 min-10 min.

Citation Information

Patent Citations

  • Method for preparing nano PCBN (Polycrystalline Cubic Boron Nitride) composite sheet from nano CBN powder at high temperature and high pressure

    CN115677354A

  • Method for preparing high-performance PcBN cutter from quinary copper-based pre-alloy powder and titanized cBN

    CN119040721A

  • Nickel-coated hexagonal boron nitride nanosheet composite powder, preparation therefor, and high-performance composite ceramic cutter material

    WO2020155737A1

  • Alloy powder and method for preparing carbon nanotube reinforced high-strength steel composite member

    WO2024250401A1